The effect of the temperature of graphene oxide reduction on low-temperature sorption of 4He - Dolbin, A.V.; Khlistyuck, M.V.; Esel`son, V.B.; Gavrilko, V.G.; Vinnikov, N.A.; Basnukaeva, R.M.; Maluenda, I.; Maser, W.K.; Benito, A.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The sorption of 4He by graphene oxide powders thermally reduced at T = 200, 300, 500, 700, 900 ºC has beeninvestigated in the interval 1.5–290 K. The measured dependence of the quantity of sorbed helium upon the reduction temperature shows up as a nonmonotonic curve. The highest quantities of helium were sorbed by the samples reduced at T = 300 and 900 ºC. It is assumed that the thermal reduction of graphite oxide by heating it to 300 ºC causes evaporation of the water intercalated in the spacings of the carbon layers, this results in exfoliation of the graphene planes, which enhances the sorptive capacity. Heating the samples to 900 ºC generates numerous defects in the carbon planes, as a result, the interlayer spacings become accessible for sorption, which enhances the sorptive capacity.